Correlations between agronomic characters in garlic - Santos, Marcelo Augusto Vieira; Andrade Júnior, Valter Carvalho de; Guimarães, Amanda Gonçalves; Brito, Orlando Gonçalves; Taula, Antônio Jorge Viegas; Costa, Rogers Augusto; Alves, João Pedro Rocha; Silva, Natália Oliveira; Resende, Francisco Vilela (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the phenotypic correlations between agronomic characters of garlic (Allium sativum) and to carry out the path analysis, using commercial bulb yield as the main character. The experiment was conducted under field conditions in two harvests (2018 and 2019) in the municipality of Diamantina, in the state of Minas Gerais, Brazil. A total of 13 garlic genotypes were evaluated, of which 11 were experimental and 2 were commercial cultivars. The experimental design used was randomized complete blocks with four replicates. Characters related to plant biometry and bulb yield were evaluated. The phenotypic correlations and the path analysis of the studied characters were carried out. The phenotypic correlations that showed significant positive effects occurred between commercial bulb yield and plant height, bulb diameter, number of commercial bulbs, mean total bulb mass, mean commercial bulb mass, total bulb yield, and number of bulbils per bulb. However, only number of commercial bulbs and bulb diameter had significant effects (direct and indirect) on commercial bulb yield. Therefore, in genotype genetic breeding programs in the studied region, selection should seek a larger diameter of bulbs and a higher number of commercial bulbs to increase commercial yield.